2011
DOI: 10.1038/ki.2011.17
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor-α is renoprotective in doxorubicin-induced glomerular injury

Abstract: Doxorubicin (DOX) is an anthracycline antibiotic utilized in antitumor therapy; however, its clinical use is frequently impeded by renal toxic effects. As peroxisome proliferator-activated receptor-α (PPAR-α) has renoprotective effects in drug-related kidney injuries, we tested its ability to inhibit DOX-induced renal injury. Although both male PPAR-α knockout mice and their wild-type littermates (pure 129/SvJ background) had significant proteinuria 4 weeks after DOX treatment, those with deletion of PPAR-α ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 36 publications
2
46
0
Order By: Relevance
“…Our results reinforce the importance of mitochondria as one of the key components of this complex and a major part of the multifactorial complications of diabetes (9,10,38,39). This study underscores previous observations by our group and others that improving mitochondrial function, by targeting mitochondrial dynamics, activity, or numbers, is renoprotective in different models of kidney injury, including DN (12,(40)(41)(42)(43)(44)(45)(46)(47)(48). We provide evidence that PGC-1α is a mechanistic target of Tug1 in podocytes in the kidney, through which Tug1 regulates mitochondrial bioenergetics.…”
Section: Methodssupporting
confidence: 76%
“…Our results reinforce the importance of mitochondria as one of the key components of this complex and a major part of the multifactorial complications of diabetes (9,10,38,39). This study underscores previous observations by our group and others that improving mitochondrial function, by targeting mitochondrial dynamics, activity, or numbers, is renoprotective in different models of kidney injury, including DN (12,(40)(41)(42)(43)(44)(45)(46)(47)(48). We provide evidence that PGC-1α is a mechanistic target of Tug1 in podocytes in the kidney, through which Tug1 regulates mitochondrial bioenergetics.…”
Section: Methodssupporting
confidence: 76%
“…Fenofibrate was reported to protect podocytes from doxorubicin-induced injury [17] but until today there are no reports to clearly state that fenofibrate alone can differentiate podocytes. We demonstrated that fenofibrate treated E11 podocytes showed morphological change resembling those reported for the differentiation of E11 podocytes by the conventional method [12, VAMP2 interactions [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, under these conditions, we are not able to perform the experiments combined with transient transfection by electroporation because the expressed protein will start to diminish 48 21]. Fenofibrate is a selective peroxisome proliferator-activated receptor-α (PPARα) agonist that is renalprotective and attenuates doxorubicin-induced podocytes foot process effacement [17]. However there are no reports studyting whether PPARα agonist affects podocytes differentiation.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…PPAR-α has renoprotective effects in drug-associated kidney injury. PPAR-α deficiency exacerbates doxorubicin-associated renal injury, in part through increasing podocyte apoptosis (22).…”
Section: Si-h-fabp Reduces Pa-induced Oxidative Stress In Podocytesmentioning
confidence: 99%